The Influence of Social Media Usage on Academic Performance among Nursing Students in University of Luzon - Lomibao, Khyra Joy; Sunga, Roma; Ramales, Louise; Geminiano, Angel; Rodas, Medmike; Santos, Grace; Beltran-Villar, Johanna (Celebes Nursing Journal, 2024)
Introduction: Recent developments and advancements in mobile phone usage and accessibility to the Internet have resulted in a dramatic increase in social media use. The use of social media, along with the different social media applications that have been continuously created, has increased significantly, and it has become one of the most dominant influences on society in current times.  There has been a rapid increase in the use of these social media applications, which has influenced many people’s daily lives, particularly in education. However, these influences come with the caution that uncontrolled use of these platforms can pose a threat and negatively affect students’ academic performance. Objective: The aim of the study is to determine the influence of social media usage on academic performance among nursing students at the University of Luzon. Methods: A questionnaire was used to collect quantitative data from the respondents. The study used total enumeration sampling to ensure that the entire population with the same characteristics as the target respondents was given a chance to answer during data collection through an online survey among 122 students. Result: The results depict that the majority of the students use social media for 5 hours or more on a daily basis, with academic grades ranging from 75.00-92.60. This study also illustrates the student’s perceptions of social media use, including the different areas of the nursing field such as academic engagement, skills laboratories, and related learning experiences. Conclusion: The study, however, concluded that there is no significant relationship between social media use and the academic performance of nursing students.